(untitled) (Zaporizhzhia Historical Review, 2021)
In article is examined such kind of source of socio-economic history of the Russian Empire and the Southern Ukraine as ‘revizskie skazki’. Author also has regarded the peculiarities of the formation of ‘revizskie skazki’ in different years and its informational possibilities as the source of socio-economic history of the Russian Empire and the Southern Ukraine in the I-st half of the ХIХ-th century.